Pengaruh Budaya Organisasi dan Komitmen Organisasi Terhadap Kinerja Pegawai Badan Promosi dan Perizinan Penanaman Modal Daerah Provinsi Sumatera Selatan - Yusuf, Muhammad (Jurnal Publisitas, 2020)
This study aims to determine the influence of organizational culture and organizational commitment to employee performance Licensing Agency for the Promotion of Regional Investment South Sumatra Province, either partially or simultaneously. The method used is descriptive method with multiple regression analysis techniques. The data source is the Whole Employee Promotion Board and Licensing Investment South Sumatra Province. The research population is Employee Promotion Board and Licensing Investment South Sumatra Province, totaling 60 people. The results of this study showed that simultaneous organizational culture and organizational commitment has influence on employee performance and Licensing Agency for the Promotion of Regional Investment South Sumatra Province. Partially organizational culture and organizational commitment has influence on employee performance and Licensing Agency for the Promotion of Regional Investment South Sumatra Province. Variable organizational culture has a dominant influence on employee performance and Licensing Agency for the Promotion of Regional Investment South Sumatra Province.